The establishment and activities and the pioneers organization in bourgeois Lithuania (1923–1940) - Savickytė, V. (Psichologija, 1964)
The first children's communist groups, called Spartacus, began in bourgeois Lithuania as early as 1923. On December 20, 1923, the Lithuanian Komsomol Central Bureau discussed the activities of these groups. Because both children and youth belonged to these groups the CB decided to single out children's group, which was for those under 14. Therefore, December 20, 1923, is considered to be the pioneer organization's founding day in the Lithuanian SSR.Since 1924 the pioneer organization began to use all legal means of action. In August 1926 it held its first general Lithuanian pioneers conference, which elected a central leadership.After the fascist coup of pioneers organization had to go underground. The 1932 Lithuanian Communist Party Central Committee plenum recommended the Communist Youth League organizations use all possible legal ways of working with children. As part of the instructions of the Party, Komsomol organizations improved work with children, because as early as in 1937 Komsomol organized activities attended by 600-700 children.
Keywords: pioneers and pioneer activity